Influence of support textural property on CO2 to methane activity of Ni/ SiO2 catalysts - Cherevotan, Arjun; Ray, Bitan; Churipard, Sathyapal R.; Kaur, Komalpreet; Gautam, Ujjal K.; Vinod, Chathakudath P.; Peter, Sebastian C. (Applied Catalysis B-Environmental, 2022)
In this work, we elucidated the role of physicochemical textural properties of inert support on the catalyst ac-tivity by impregnating Ni on ordered mesoporous silica (SBA-15 and MCM-41) and non-mesoporous silica (nMPS). The catalyst Ni/SBA-15 exhibited the best CO2 conversion (83%) and product selectivity (99.9 %) followed by Ni/MCM-41 and the least by Ni/nMPS. The difference in the nature of the catalyst, degree of nanoparticle distribution and nanoparticle encapsulation by different silica support were studied by N2 adsorption-desorption and X-ray photoelectron spectroscopy (XPS) experiments. The Operando Diffused Reflec-tance Infrared Fourier Transform Spectroscopy were used to understand the variance in reaction pathway which is accredited to the textural properties of the support. The SBA-15 supported Ni catalyst followed dissociative CO pathway while MCM-41 and nMPS reacted through associative formate mechanism as major pathway. These findings provide a novel perspective on CO2 hydrogenation over Ni-silica, allowing us to tune both activity and selectivity.
Keywords: CO2 methanation; DRIFTS; Mesoporous silica support; Textural properties